GARAP RICIKAN NGAJENG GENDING GAMBIRSAWIT PADA KARAWITAN GAYA SURAKARTA - Yadi (BBPPMPV Seni dan Budaya Yogyakarta, 2022)
“Gambirsawit” is one of the styles of Surakarta traditional music composed by SunanKalijaga at the time of the spreading of Islam. The song is taken from the song “PathetanWantah Laras Slendro Pathet Sanga”. In its development, there were some titles of various“gending” using “Gambirsawit” as the first name of the “gending”. The examples of thesongs in question are “Gambirsawit Pancerana” and “Gambirsawit Sembunggilang”. Thereare also two “gending” which shift the musical scale of “Gending Gambirsawit”, namely“Gending Malarsih Laras Slendro Pathet Manyura “and “Gending Prawan Pupur LarasPelog Pathet Barang”. In addition to having various names, “Gending Gambirsawit” in itspresentation also has various “garap” (creating composition of ”gending”), one of which is“garap ricikan ngajeng”. The aim of the current study is to find out and describe the musicalcomposition of “Gending Gambirsawit” in “ricikan ngajeng” of Surakarta style “karawitan”.Qualitative research method was applied to analyze data collected through literature study,interviews, observation, and listening to “gending” recordings. The results of the study arepresented in the description of “garap” (musical composition) of “ricikan ngajeng GendingGambirsawit” including musical composition or “garap” of “rebab”, “kendang”, “gender”,and vocal. “Garap” on “ricikan ngajeng” can be performed in the presentation of “GendingGambirsawit” for musical concerts, “pakeliran” accompaniment, and dance accompaniment.Keywords: musical composition (“garap”), “gending”, “Gambirsawit”, “karawitan”.ABSTRAKGambirsawit merupakan salah satu gending tradisi gaya Surakarta yang disusun oleh SunanKalijaga pada saat menyebarkan agama Islam. Gending ini diambil dari lagu Pathetan WantahLaras Slendro Pathet Sanga. Dalam perkembangannya, muncul beraneka ragam namagending yang menggunakan Gambirsawit sebagai nama awal dari gending tersebut. Contohgending-gending yang dimaksud adalah Gending Gambirsawit Pancerana dan GendingGambirsawit Sembunggilang. Selain itu, ada dua gending yang oleh para pengrawit disebutsebagai alih laras dari Gending Gambirsawit. Gending tersebut adalah Gending MalarsihLaras Slendro Pathet Manyura dan Gending Prawan Pupur Laras Pelog Pathet Barang.Selain memiliki berbagai nama, Gending Gambirsawit juga memiliki berbagai garap dalampenyajiannya; salah satunya adalah garap ricikan ngajeng. Tujuan penelitian ini adalah untukmenemukan dan mendeskripsikan garap musikal Gending Gambirsawit pada ricikan garapngajeng karawitan gaya Surakarta. Metode kualitatif deskriptif digunakan dalam penelitian iniuntuk mengolah data yang dikumpulkan melalui studi pustaka, wawancara terhadap tokohtokoh bidang karawitan, pengamatan sajian kelompok-kelompok karawitan, dan denganmendengarkan hasil rekaman. Hasil penelitian berupa deskripsi garap musikal GendingGambirsawit ricikan ngajeng yang meliputi garap instrumen rebab, kendang, gender, dan garap vokal. Garap tersebut dapat ditampilkan dalam penyajian Gending Gambirsawit untukkonser karawitan, iringan pakeliran, dan iringan tari.Kata kunci: garap, gending, Gambirsawit, karawitan.